If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + 3) = 9x Reorder the terms: 3(3 + 4x) = 9x (3 * 3 + 4x * 3) = 9x (9 + 12x) = 9x Solving 9 + 12x = 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 9 + 12x + -9x = 9x + -9x Combine like terms: 12x + -9x = 3x 9 + 3x = 9x + -9x Combine like terms: 9x + -9x = 0 9 + 3x = 0 Add '-9' to each side of the equation. 9 + -9 + 3x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 3x = 0 + -9 3x = 0 + -9 Combine like terms: 0 + -9 = -9 3x = -9 Divide each side by '3'. x = -3 Simplifying x = -3
| 2=3(4n-6)+8(5n-4) | | 4t-7=10t+5 | | 4x+3-5=29 | | x^2-x+6= | | 6x+7=42-x | | -9=-(1+8x)-2(4-4x) | | 7+x=.5(4*-2) | | 12x-4=5x-32 | | 3x+5+2x=54 | | 7x+20= | | 2x^2-17x+15=0 | | 5y+3=9y-1 | | 7+x=.5(4*2) | | 5x-1=3x+13 | | 5-4k=-(4k+1) | | 6x-12+3x+26=180 | | z^2(x+1)-3z(x+1)-70(x+1)=0 | | (1.1+k)5-7.6=1.6 | | d-4=-13 | | -2(w-7)+lOw=34 | | 7x+2y=7 | | 17+3(z+2)-11z=-7(z+2)+14 | | 20x+53= | | 2p-(1+8p)=4p-21 | | (15-y)+2=2y | | -2x+3=4x+75 | | Y+7-3=12 | | xz^2+z^2-3zx+4z-70x+70=0 | | 200-80=2l+80-80 | | 8r+7=49 | | s=p(1+rt) | | 14+s=-32 |